Button battery exposures in Australian children: a prospective observational study highlighting the role of poisons information centres. (3rd June 2019) - Cairns, Rose; Brown, Jared A.; Lachireddy, Kishen; Wylie, Carol; Robinson, Jeff; Dawson, Andrew H.; Buckley, Nicholas A.
Abstract: Context: Button battery ingestion is a worldwide problem, with evidence of increasing harms and deaths in recent decades. Australian Poisons Information Centre (PIC) experience includes cases of treatment delay due to lack of healthcare professional recognition of risks, and/or lack of local resources. This study aims to characterise Australian button battery exposures, focusing on exposure circumstances, and preventable health system shortcomings. Methods : A prospective observational study of button battery exposure calls to New South Wales PIC, November 2015–May 2017, using a follow-up survey to obtain outcome data and additional details. Survey data was combined with nationwide PIC data over the same period. Results: Australian PICs were consulted on 578 exposures over the 19-month study period, including 506 paediatric cases. The median (IQR) age for the paediatric cases was 23 months (14–36 months). Where the source was identified, batteries came from toys in 26% of cases, with hearing aids, watches, and remote controls being other common sources. Children in outer regional, remote and very remote areas were overrepresented, and 15 cases were referred to a different hospital due to X-ray facilities being unavailable at their nearest hospital. We identified inconsistent triage from a range of first responders, and knowledge gaps regarding button battery dangers amongst some healthcare professionals. Discussion: Button battery exposures are a common call to Australian PICs. This study highlights a potential role of education campaigns, professional guidelines, and child-resistant battery compartments in toys and household devices. PICs calling ahead to ensure X-ray availability/ diversion to a different hospital likely reduced delays for this time-critical exposure. Conclusions: Button battery exposures continue to be a problem in Australia. Data collected by PICs can provide useful information for public health and product safety initiatives. A PIC-led protocol to direct initial medical management of button battery exposures could reduce delays and improve outcomes.